REGIONAL ECONOMIC DEVELOPMENT IN UZBEKISTAN: DIFFERENCES BETWEEN THE CENTER AND OUTER REGIONS (Marketing Journal, 2025)
This study presents a comprehensive analysis of regional socio -economic development in Uzbekistan from 2020 to 2024, with a particular focus on disparities between central and peripheral areas. Key indicators analyzed include Gross Regional Product (GRP), real per capita income, employment rate, and poverty level. By applying statistical techniques such as the Shapiro –Wilk test, logarithmic transformation, ANOVA, and the Kruskal –Wallis test, the research identifies significant differences across regions. Fi ndings reveal a generally positive trend in development, though economic gaps remain prominent, particularly in income distribution and employment rates. Tashkent city, along with Navoiy and Tashkent regions, lead in economic performance, while other areas lag behind. Notably, the national decline in poverty and rising incomes demonstrate the tangible impact of economic reforms. The study offers valuable insights for policymakers in tailoring region -specific development strategies to ensure balanced and inc lusive growth.
Keywords: Region; development; population; GRP; unemployment; employment; poverty; income; center; economic imbalance; industry; strategy; sustainability